"Chessboard" effect and mass transfer in interfacial media of organic and inorganic nature; Physical Mesomechanics; Vol. 11, iss. 1-2, Jan.-Apr - Panin L. E. (2008, 2008)
The paper reviews our previous research work on the origin of mass transfer through interfaces of solids and biological membranes. Using the thermodynamic approach of physical mesomechanics we conclude that the propagation of transport flows through interfaces and membranes in organic and inorganic nature is based on structural phase transformations in nanostructural states at interfaces of heterogeneous media. Such states arise at interfaces and in membranes under a chessboard-like distribution of stresses, strains and chemical potentials of components of conjugated dissimilar media. The practical applications of the developed approach in biology and modern materials science are considered